2015
DOI: 10.1002/hyp.10506
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the longitudinal stream temperature paradigm: region-wide comparison of thermal infrared imagery reveals unexpected complexity of river temperatures

Abstract: Prevailing theory suggests that stream temperature warms asymptotically in a downstream direction, beginning at the temperature of the source in the headwaters and levelling off downstream as it converges to match meteorological conditions. However, there have been few empirical examples of longitudinal patterns of temperature in large rivers due to a paucity of data. We constructed longitudinal thermal profiles (temperature vs distance) for 53 rivers in the Pacific Northwest (USA) using an extensive data set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 73 publications
4
128
0
1
Order By: Relevance
“…Taking into account the uncertainties, the groundwater discharge calculated through the heat budget always remained positive between river kilometers 636 and 645. This river section corresponds to a known discharge area of the Beauce aquifer and the Val d'Orléans hydrosystem (Desprez and Martin, 1976;Gonzalez, 1991;Binet et al, 2011), which is also identified by groundwater modeling (calculated discharge was between 0.6 and 0.9 m 3 s −1 km −1 ). Schomburgk et al (2012) calculated a slightly lower but still significant groundwater discharge of 0.5 m 3 s −1 km −1 .…”
Section: Longitudinal Temperature Profiles and Groundwater Discharge mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the uncertainties, the groundwater discharge calculated through the heat budget always remained positive between river kilometers 636 and 645. This river section corresponds to a known discharge area of the Beauce aquifer and the Val d'Orléans hydrosystem (Desprez and Martin, 1976;Gonzalez, 1991;Binet et al, 2011), which is also identified by groundwater modeling (calculated discharge was between 0.6 and 0.9 m 3 s −1 km −1 ). Schomburgk et al (2012) calculated a slightly lower but still significant groundwater discharge of 0.5 m 3 s −1 km −1 .…”
Section: Longitudinal Temperature Profiles and Groundwater Discharge mentioning
confidence: 99%
“…Until now, these images of watercourses have mainly been used (i) to identify cold refuges for fish in the summer (Belknap and Naiman, 1998;Torgersen et al, 1999;Tonolla et al, 2010;Monk et al, 2013); (ii) to study the thermal variability of rivers or alluvial floodplains and locate areas of similar thermal characteristics (Smikrud et al, 2008;Tonolla et al, 2010;Wawrzyniak et al, 2012, Fullerton et al, 2015; and (iii) to validate river temperature models (Boyd and Kasper, 2003;Cristea and Burges, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, airborne thermal imagery has revealed the need to reconsider the dominant paradigm of longitudinal stream water temperature profi les because the mean temperature does not always rise asymptotically with river length [13]. Despite the signifi cant benefi ts of remote sensing, it must be emphasized that such techniques are expensive and hard to apply in the case of small rivers covered by riparian shade [14].…”
mentioning
confidence: 99%
“…Although originally counterintuitive, salmonids are often found to be more strongly related to physical features that emerge at riverscape scales than to factors measured at local scales (e.g., Fausch et al 2002b;Isaak et al 2007;Flitcroft et al 2012;Falke et al 2013). Ongoing research in this arena, including advances in methods for measuring and modeling habitats across the entire spatial hierarchy (Peterson et al 2013;Fullerton et al 2015), will continue to yield insights and improve management of salmonids in riverscapes.…”
Section: Contributions In Three Subdisciplines Of Ecologymentioning
confidence: 99%